Effect of Hot-rolling Deformation on Microstructure and Mechanical Properties of Nd2Fe14Bp/Al-5Co-0.4Sm Composites - Jun-jie, Huang; You-wei, Huang; Jia-xin, He; Ma, Kang; Hong-ming, Wang (Journal of Chemical Engineering Research Updates, 2024)
Nd2Fe14Bp/Al-5Co-0.4Sm composites were prepared via microwave sintering and hot rolling. The effects of hot-rolling deformation on the microstructure and mechanical properties of Nd2Fe14Bp/Al-5Co-0.4Sm composites were studied. The results showed that the internal porosity of the composites significantly decreased when the hot-rolling deformation rate was 45%. The Nd2Fe14B particles were broken into fine particles under rolling stress. Consequently, the particles were uniformly distributed. Moreover, numerous high-density dislocations were observed around the particles, which improved the strength and toughness of the material. When the deformation rate was 45%, the micro-nano hardness and elastic modulus of the interface of the composites were 3.6 and 91 GPa, respectively. The interfacial deformation resistance of the composites was significantly higher than that of the composites before rolling. The tensile strength of Nd2Fe14Bp/Al-5Co-0.4Sm composites increased as the deformation rate increased, whereas the elongation gradually decreased. Furthermore, when the deformation rate was 45%, the tensile strength and elongation of the composites were 161 MPa and 6.5%, respectively. The tensile strength was 14.2% higher than that of the unrolled sample.